Ionic Transport and Charge Distribution in Miniaturized Electrochemical Energy Storage Devices by Modeling Investigation. Issue 6 (1st June 2022) - Dufil, Yannick; Favier, Frederic; Brousse, Thierry; Lethien, Christophe; Le Bideau, Jean; Fontaine, Olivier
Abstract : Ions are at the core of the mechanism involved in electrochemical energy storage. However, it remains difficult to physically measure the local ionic transport inside working devices. Limiting factors in the local transport in Miniaturized Electrochemical Energy Storage (MEES), especially in 3D Li-ion microbatteries, are investigated using finite element modeling with COMSOL Multiphysics®. This work aims to lay the basements for establishing a relationship between the main limiting factors of Li-ion microbatteries, to provide the critical points for designing the efficient microstructures. Contrary to what was reported in the literature, we demonstrate that the electronic conductivity of the electrodes does not play such a significant role in limiting the performance of a Li-ion microbattery. We show that the main limiting factor is the ionic diffusion inside the electrode, and also the geometry and charge applied to the battery (Crate) which are closely related to ionic diffusion in the electrode.